2021
DOI: 10.1101/2021.04.26.441488
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Loss ofMafbandMafdistorts myeloid cell ratios and disrupts fetal mouse testis vascularization and organogenesis

Abstract: Testis differentiation is initiated when Sry in pre-Sertoli cells directs the gonad toward a male-specific fate. Sertoli cells are essential for testis development, but cell types within the interstitial compartment, such as immune and endothelial cells, are also critical for organ formation. Our previous work implicated macrophages in fetal testis morphogenesis, but little is known about genes underlying immune cell development during organogenesis. Here we examine the role of the immune-associated genes Mafb… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 89 publications
(116 reference statements)
1
4
0
Order By: Relevance
“…However, we observed numerous CD11b+ myeloid cells in the gonad- mesonephros border region. In our recently published results (25), gonads lacking Mafb and Maf (also called c-Maf ), encoding transcription factors required for monocyte/macrophage development (6769), also exhibited extensive supernumerary CD11b+ cells, and we demonstrated that these CD11b+ myeloid cells are monocytes; however, F4/80+ macrophages were not affected in Maf and Mafb mutant gonads.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…However, we observed numerous CD11b+ myeloid cells in the gonad- mesonephros border region. In our recently published results (25), gonads lacking Mafb and Maf (also called c-Maf ), encoding transcription factors required for monocyte/macrophage development (6769), also exhibited extensive supernumerary CD11b+ cells, and we demonstrated that these CD11b+ myeloid cells are monocytes; however, F4/80+ macrophages were not affected in Maf and Mafb mutant gonads.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, the reduction of steroidogenic gene expression in CSF1R-antibodyinjected E18.5 testes may be related to the enhanced phagocytic activity of repopulated excess testicular macrophages and monocytes. In Maf mutant fetal gonads, we also found there were numerous monocytes with a downregulation of many steroidogenic genes (25). Therefore, a balance between Leydig cell steroidogenesis and testicular macrophage proliferation is critical for testis development and function.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Vascularization is crucial for the delivery of exogenous factors in the testicular compartments, in the initial organization of the testis cords, and also in the regulation of testis morphogenesis (Gu et al, 2021; Singh and Modi, 2020; Svingen and Koopman, 2013). It is also required for maintaining the interstitial progenitor population of the fetal Leydig cells (Gu et al, 2021; Kumar and DeFalco, 2018; Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%